Investigation of compressive strength foam brickwall panel with different bonding by using stretcher & flemish bond - Sukri, Deraman (2010)
Today, there are many types of masonry units that are available in the market which varies in shapes and sizes. Clay bricks are the most widely used masonry units for construct brick wall in construction industry. In developing construction industry, many alternative materials had used to replace the clay brick, such as foam concrete brick. A study to determine the compressive strength of foam concrete brick wall due to uniform distribution load by using Stretcher and Flemish bond was done. Various sets of wall panels using Stretcher and Flemish bond were made and have same dimension based on bonding type. In this research, the brick size used is based on standard dimension by British Standard which is 215 x 100 x 65 mm. The wall panels were tested to obtain the necessary information. Laboratory testing was done to obtain the compressive strength of wall panel for Stretcher and Flemish bond by using compressive strength test. The value of deflection and strain also obtained from the testing. Percentage of water absorption for foam concrete brick is determined by using water absorption test. Observation also was made during the test to evaluate the failure occurred to the wall panel under compression. From the observation made during the testing, the general failure mode occurred on the wall panel sample are obtained. The result indicated from the test and analysis had determined the compressive strength of wall panel sample, deflection, and strain for Stretcher and Flemish bonding.